AMFC tool: Auditing and monitoring for cloud computing - Pauro, Leandro [UNESP]; Spolon, Roberta [UNESP]; Bruschi, Gustavo [UNESP]; Manacero, Aleardo [UNESP]; Lobato, Renata [UNESP]; Cavenaghi, Marcos (Springer Nature, 2019)
Cloud Computing has been increasingly incorporated by companies as a cost-effective way to make resources and services continuously available. However, as a consequence of service downtimes at cloud providers, achieving operational reliability and resource availability are still a concern, since they can lead to loss of revenue and customer mistrust. This work presents Apache CloudStack AMFC (Auditing and Monitoring For Cloud Computing), a cloud auditing and monitoring tool aimed to perform the removal of unused data and inconsistencies, improve failure detection (reducing false positive and false negative alerts), and reduce the cost for storing persistent cloud data. All these characteristics are achieved through the synchronization of current state information with persistent orchestration data. The effectiveness of the tool is evidenced through testing on experimental scenarios generated in a controlled test environment. The experiments involved 1,320 administrative routines for virtual machine instances. It was possible to identify and eliminate inconsistencies in the persistent database, allowing a reduction in the storage cost and, consequently, an improvement on database integrity. Overall, the AMFC provided the cloud administrator with more accurate data, enhancing decision-making, allowing a better identification of problems occurring in the cloud environment.
Keywords: Cloud computing; Inconsistency; Monitoring